Mechanical and Thermal Behaviour of Ecofriendly Composites Reinforced by Kenaf and Caroà Fibers - P. Persico; D. Acierno; C. Carfagna; F. Cimino (International Journal of Polymer Science)
Two kinds of environmental friendly composites were prepared based on sustainable matrices, respectively, defatted cross-linked soy flour and thermoplastic polyhydroxybutyrate cohydroxyvalerate, reinforced by natural fibers from Caroà and Kenaf plants. The obtained composites were compared in terms of moisture tolerance, thermal and mechanical properties, and thermoregulation ability. It was found that this ecofriendly systems have suitable properties for indoor applications in housing and transportation.